Analisis Hubungan Panjang Tubuh Dengan Tingkat Kematangan Gonad Dan Estimasi Ukuran Pertama Kali Matang Gonad (L50) Pada Ikan Teri (Stolephorus Indicus.) Di Perairan Gorontalo Utara - Moh Fahri; Dewi Shinta Achmad; Tusaban; Nur Jihan Fareranty Piu (Jurnal Akuakultur Rawa Indonesia, 2026)
This study aimed to determine the size at first sexual maturity (L50) of Stolephorus indicus in the waters of North Gorontalo and to analyze its relationship with gonadal maturity through biological and statistical approaches. A total of 2,061 specimens were randomly collected from lift-net (bagan perahu) catches, after which each fish was measured for total length and dissected to identify its gonadal maturation stage. The proportion of mature individuals within each length class was then analyzed using a logistic curve to estimate the L50 value, representing the size at which 50% of the population reaches reproductive maturity. The results revealed a clear sigmoid pattern, indicating a positive correlation between body size and the proportion of mature fish; most individuals smaller than 4 cm were immature, while a significant increase in maturity occurred within the 4.5–6.5 cm size range. The estimated L50 of 5.42 cm suggests that a portion of the population is being harvested before reproducing, emphasizing the need for management measures such as implementing a minimum mesh size of 7 mm and establishing a minimum legal catch size of ≥6.5 cm to reduce juvenile exploitation and support the sustainable management of anchovy resources in North Gorontalo waters.